Interwencja triangularna i jej konsekwencje dla gospodarki - Wojtyszyn, Radosław (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
The paper is a continuation of the presentation of Rothbard’s criticism of state interventionism in economy. It is focused on its triangular version. As a triangular intervention we classify price controls, minimum wage, product regulation, including all sorts of monopolistic privileges, licenses and tariffs, production and employment standards, patents and copyright, and prohibition. The article also presents Rothbard’s views on the nature of monopoly and the possibility to create monopoly prices in the free market. Following Rothbard, we consider the mechanisms of statism and its side effects for entrepreneurial activity, violating not only the economic sphere, but also the ethics of liberty.
Keywords: Rothbard, Murray Newton (1926-1995); płaca minimalna; monopol; etatyzm